PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 32 TAHUN 2020 TERHADAP NARAPIDANA NARKOTIKA DITINJAU DARI ASAS PROPORSIONALITAS HUKUM PIDANA - Lasnita, Fiany Alifia (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2023)
This study aims to examine how the policy of granting assimilation for Narcotics Convicts during the Covid-19 pandemic based on the principle of proportionality in criminal law. This research is normative legal research with the type of approach used is a statutory approach. The legal materials of this research include primary, secondary, and tertiary legal materials. The data collection technique used is a literature study technique. The analytical technique used is the syllogistic reasoning method that uses deductive thinking patterns. The results of this study indicate that the condition of correctional institutions in Indonesia for narcotics convicts has a disproportionate or over-capacity prison capacity. the prison's disproportionate capacity or overcrowding. The Minister of Law and Human Rights Number 32 of 2020, including its restrictions on Article 11 paragraph (2) and Article 31 paragraph (2), does not pay attention to the health conditions of vulnerable convicts. Permenkumham Number 32 of 2020, if not supported by other legal policies granting assimilation of narcotics convicts, can be said to be in breach of narcotics prisoners' enshrined in the constitution rights to protect their lives. However, Permenkumham Number 32 of 2020 commits violations that are less severe than regular, and their implementation has been considered based on their benefits and advantages.